Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1111/j.1471-0528.2000.tb13269.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal dexamethasone administration on fetal Doppler flow velocity waveforms

Abstract: Objective To investigate the effects of maternal dexamethasone administration on umbilical and fetal Design Cross-sectional study.Setting Department of Obstetrics and Gynaecology, Robert Ballanger Hospital, Aulnay-sous-Bois, Sample Twenty-six pregnant women with singleton pregnancies considered at risk for preterm delivery.At baseline, all pregnancies had normal fetoplacental vascular resistance.Methods These women were given weekly six intravenous doses of 4 mg of dexamethasone eight hours apart.Main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…This effect was attributed to the action of dopamine on the dopaminergic receptors of the vessels and glucocorticoids modifying this reaction [21]. Several in vivo studies of the human fetus did not report a similar reaction of the UA after betamethasone [6,[22][23][24]. However, in these studies, no measurement was performed 30 min after betamethasone administration.…”
Section: Discussionmentioning
confidence: 79%
“…This effect was attributed to the action of dopamine on the dopaminergic receptors of the vessels and glucocorticoids modifying this reaction [21]. Several in vivo studies of the human fetus did not report a similar reaction of the UA after betamethasone [6,[22][23][24]. However, in these studies, no measurement was performed 30 min after betamethasone administration.…”
Section: Discussionmentioning
confidence: 79%
“…It had mild effect on the fetal heart rate (24). Although in some investigations, it was found that it did not affect Doppler parameters of UA, UtA, and MCA, in some, a decrease in Doppler indices of UA and MCA (25,26) and ductus venosus, particularly PI of MCA, was seen (27). Therefore, it is thought that variations in fetal and fetomaternal circulation in the late period (24-48 hours) of nifedipine and ritodrine in different studies are caused by a combined effect of tocolysis and betamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace and Baker 12 have reported that betamethasone administered during pregnancy is associated with decreased placental vascular resistance as measured by return of end-diastolic flow using Doppler ultrasonography in the umbilical artery in pregnancies complicated by absent end-diastolic flow. Similarly, after maternal dexamethasone or betamethasone treatment, a significant decrease in fetal middle cerebral artery impedance (pulsatility index) has been demonstrated in third trimester healthy fetuses 13 and in third trimester high risk pregnancies 14 . No clear explanation exists for this decreased vascular resistance but theories have focussed on the possibility that exogenous corticosteroids increase placental secretion of corticotrophin releasing hormone (CRH), which is a potent vasodilator in the fetal placental circulation 12,14,15 .…”
Section: Introductionmentioning
confidence: 96%